Advanced Oxidation Processes to Reduce Odor Emissions from Municipal Wastewater—Comprehensive Studies and Technological Concepts - Marcin Dębowski; Joanna Kazimierowicz; Marcin Zieliński (Atmosphere, 2022)
Municipal facilities can generate odors caused by substances such as fatty acids, organosulfur compounds, aldehydes, and inorganic gases, especially H2S. Identifying an effective and cost-efficient solution to the problem is a priority for communities in areas at risk of exposure to odors. The aim of this study was to evaluate the effect of advanced oxidation processes (AOPs) involving Fenton’s reagents (Fe2+/H2O2, Fe3+/H2O2) on wastewater profiles and their capacity to reduce putrescibility, H2S emissions, and odor concentration in the air. The Fe2+/H2O2 system proved to be the most efficient in terms of inhibiting the process of redox conditions development, removing organic matter in the wastewater, inhibiting H2S formation, and reducing odor emissions. H2S generation in raw wastewater was triggered as early as on day 2 of anaerobic retention, with levels of 5.6 ppm to 64 ppm. After introduction of 0.1 g Fe2+/dm3 and 2.0 g H2O2/dm3, no H2S was detected in the gas for 8 days. The odor concentration (OC) of raw wastewater (2980 ± 110 oue/m3) was reduced by 96.3 ± 1.9% to a level of 100 ± 15 oue/m3. The Fe2+/H2O2 system maintained its oxidizing capacity up until day 7, with OC reduction by 96.0 ± 0.8% to a level of 120 ± 10 oue/m3. On day 10, the OC showed a marked increase to a level 1310 ± 140 oue/m3. The conducted research has proven that Fenton-based AOP systems are a technologically and commercially viable method of deodorization of sewage facilities.